Legal Structuring of Public Infrastructure Projects: A Practical Guide for Government Lawyers and Project Teams - Ayibam, Joanna Nyaposowo (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2024)
Public infrastructure projects are critical to economic development, yet their success often hinges on effective legal structuring to mitigate risks and ensure compliance. Government lawyers and project teams face multifaceted legal challenges, from procurement and contract negotiations to risk allocation and dispute resolution. This paper provides a practical guide to navigating the legal complexities of infrastructure projects, emphasizing the importance of early legal intervention in project planning and execution. The first section explores the intricate legal landscape of infrastructure projects, highlighting the interplay between procurement laws, contract laws, and public-private partnership (PPP) frameworks. Subsequent sections analyze common legal pitfalls, such as ambiguous contractual terms, non-compliance with regulatory requirements, and inadequate risk-sharing mechanisms. Special attention is given to drafting robust dispute resolution clauses to minimize litigation delays and costs. Additionally, the paper underscores the pivotal role of legal advisors in contract review, risk assessment, and ensuring alignment with governmental policies. By integrating legal expertise from the outset, project teams can enhance transparency, accountability, and project sustainability. The conclusion reinforces the argument for proactive legal involvement, demonstrating how early engagement can prevent costly disputes and foster successful project outcomes. This guide serves as a valuable resource for government lawyers, policymakers, and infrastructure project teams seeking to strengthen legal frameworks and optimize project delivery.